Sustainability as a trend for competitiveness challenges - Ştefănescu, Mihaela (Cambridge Scholars Publishing, 2019)
Defining a future development pathway through the lens of sustainability and competitiveness is a unique trademark of any free market. Going beyond this aspect, this book is an invitation to identify relevant correlations between the circular economy, trade, adaptation to climate change, land degradation neutrality, fair-trade, corporate social responsibility, culture, and gender. Among all of these sectors, we are currently witnessing various types of synergies. The key is to distinguish those adaptive solutions which are applicable to real-time changes. This volume scrutinizes the role playe.